(untitled) (Architecture Image Studies, 2023)
Edirne, which was founded on the roads connecting the Asian and European continents, has been an important crossing point since the earliest times in history and has hosted various civilizations for centuries and has acquired a rich historical knowledge. Edirne, which was conquered by the Ottoman Empire in 1361 and later became the capital of the Ottoman Empire for approximately ninety years, has become a prominent center with its natal structure as well as politically and culturally, as it is the capital. After the Ottomans took the city, great importance was given to urban development, and water structures were built, especially the Selimiye and Eski, Üç Şerefeli Mosques, where many people stayed. The city of Edirne meets its water needs from the water resources around the city. The water from these sources is carried to the city through aqueducts and maksems, and their distribution within the city is provided by fountains. These fountains in the city house are small structures and are important structures in terms of the progress of their features. It continues to be built for six hundred years, pieces exceeding thousands; However, these water structures, a small part of which survives today, has preserved the social and aesthetic strength of the city. This article aims to express the place of the structure in the history of the city and to explain the processes of examination, research and repair work carried out on three fountain structures during the 16-year and 18-year period of the project, located in the Central District of Edirne Province.